P68 Disease burden, treatment, and health care utilisation of COPD patients by their GOLD classification in the U.K. (December 2018) - Sansbury, LB; Anley, G; Bains, C; Ho, S; Ismaila, A
Abstract : Introduction and objectives: The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2017 strategy for prevention, diagnosis and management of COPD categorises patients into four groups (Groups A-D) based on spirometrically confirmed diagnosis, assessment of airflow limitation, and assessment of symptoms and risk of exacerbations. The report suggests a pharmacologic treatment algorithm for each group at a therapeutic class level. However, prescribing for COPD is not always aligned with these recommendations (Asche CV, 2012; Visentin E, 2015). This population-based observational study characterises the U.K. COPD population, using the GOLD 2017 definitions, and describes the prescribing practices and distribution of patients across the four groups. Methods: A retrospective cohort analysis included COPD patients aged ≥35 years with at least one FEV1 % predicted value and MRC dyspnoea score recorded between 31st May 2011 – 1st June 2017. These scores along with exacerbation history defined the patient's GOLD 2017 classification. Patients were identified using U.K. Clinical Practice Research Database (CPRD). Patients were followed for 12 months to describe disease burden, treatment, and healthcare utilisation. Results: Among the 42 331 eligible COPD patients (mean (SD) age: 69.4 (10.7), 54% males), GOLD 2017 categorizations were: Group A (low risk (for COPD exacerbations), less symptoms): 49.1%, Group B (low risk, more symptoms): 30.5%, Group C (high risk, less symptoms): 8.2%, Group D (high risk, more symptoms): 12.1% (table 1). The most commonly prescribed maintenance therapy for Group A and B patients was a dual inhaled corticosteroid +long acting b2 agonist (ICS/LABA) (table 1). We observed that over half of the patients categorized in Group D (58.0%) received a prescription for triple therapy, defined by inhaled corticosteroid +long acting b2 agonist +long acting anti-muscarinic (ICS/LABA/LAMA), as well as 36.9% and 36.1% of Group B and C patients, respectively (table 1). Conclusion: This large observational study illustrates the categorisation of COPD patients according to GOLD 2017, in U.K. general practice. Among patients who were categorised as GOLD D, over half received a prescription for triple therapy and experienced the largest burden of exacerbations. A third of patients in Groups B as well as C also received a prescription for triple therapy. Funding: GSK (Study PRJ2547, ISAC 17_720)